[Waders and seabirds (Charadriiformes) nesting along the north-eastern Adriatic coastline (Veneto and Friuli-Venezia Giulia) in 2008-2014: abundance, trends and major conservation issues] - Francesco Scarton; Emiliano Verza; Carlo Guzzon; Paolo Utmar; Giacomo Sgorlon; Roberto Valle (Rivista Italiana di Ornitologia, 2019)
[In 2008-2014 wader and seabird nesting pairs were censused along the 220-km long coastline of the NE Adriatic Sea, in the Veneto and Friuli-Venezia Giulia regions (NE Italy). Fourteen species were regularly breeding, with an annual mean of 20,610 pairs (±1553, 1 SD). The most abundant species was the Yellow-legged Gull (about 13,400 pairs on average, 65% of the whole population of the study area), followed by the Common Tern (1670 pairs, 8.1%) and Common Redshank (1525 pairs, 7.4%). The whole population of waders and seabirds increased with an annual rate, estimated with the TRIM software, of +0.8%, with a greater increase (+4.3%) if the Yellow-legged Gull was not included. Twelve species were stable or increasing; only the yellow-legged gull (-1%) and the common redshank (-2.4%) were decreasing. The populations of several species exceed 10% of those estimated for the whole of Italy; those of the Eurasian Oystercatcher, Common Redshank and Sandwich Tern are among the most important in the whole Mediterranean. On average, about 8860 pairs (43%) nest in the Venice lagoon, 6,400 pairs (31%) in the Po Delta, 5100 pairs (25%) in the Friuli-Venezia Giulia lagoons. Among nesting habitats, semi-natural (such as the fish farms) and man-made sites (dredge islands) make each year about 70% of the nesting pairs. Saltmarsh islets host large numbers of Common Redshank and Sandwich Tern, while along the beach zone the only abundant species are the Yellow-legged Gull and the Eurasian Oystercatcher. The major conservation threats observed in the study area were the erosion of littoral islands, the uncontrolled occurrence of sunbathers along the beaches, the vegetation overgrowth at dredge islands, the increasing frequency of saltmarsh submersion by high tides, the strong fluctuations of water levels inside the fish farms.] [Article in Italian]